A Relational-Constructionist Account of Protein Macrostructure and Function - Vallejos-Baccelliere, G; Vecchi, D (SPRINGER, 2020)
One of the foundational problems of biochemistry concerns the conceptualisation of the relationship between the composition, structure and function of macromolecules like proteins. Part of the recent philosophical literature displays a reductionist bias, that is, the endorsement of a form of microstructuralism mirroring an out-dated biochemical conceptualisation. We shall argue that such microstructuralist approaches are ultimately committed to a potentialist form of micro-predeterminism whereby the macrostructure and function of proteins is accounted for solely in terms of the intrinsic properties and potentialities of the components of the primary structure as if they were self-contained or essentially immutable entities. We shall instead suggest that a conceptualisation of the relationship between proteins composition, structure and function consistent with contemporary biochemical practice should account also for the causal role of the cellular, organismal and environmental relations in protein development. The analysis of the folding process we propose suggests that microstructure-laden reductionist approaches are ontologically indefensible. Rather than a potentialist form of micro-predeterminism, our analysis ultimately supports a relational-construction-based view of protein development and potentialities formation, which requires an indispensable analysis of the dynamical interplay between the micro-level of the parts and the macro-level of the relational structures of their systems.